Mechanistic studies for the role of cellular nucleic-acid-binding protein (CNBP) in regulation of c-myc transcription - Chen, Siqi; Su, Lijuan; Qiu, Jun; Xiao, Nannan; Lin, Jing; Tan, Jia-heng; Ou, Tian-miao; Gu, Lian-quan; Huang, Zhi-shu; Li, Ding (Biochimica et biophysica acta, 2013)
Guanine-rich sequence of c-myc nuclease hypersensitive element (NHE) III1 is known to fold in G-quadruplex and subsequently serves as a transcriptional silencer. Cellular nucleic-acid-binding protein (CNBP), a highly conserved zinc-finger protein with multiple biological functions, could bind to c-myc NHE III1 region, specifically to the single strand G-rich sequence. In the present study, a variety of methods, including cloning, expression and purification of protein, EMSA, CD, FRET, Ch-IP, RNA interference, luciferase reporter assay, SPR, co-immunoprecipitation, and co-transfection, were applied to investigate the mechanism for the role of CNBP in regulating c-myc transcription. We found that human CNBP specifically bound to the G-rich sequence of c-myc NHE III1 region both in vitro and in cellulo, and subsequently promoted the formation of G-quadruplex. CNBP could induce a transient decrease followed by an increase in c-myc transcription in vivo. The interaction of CNBP with NM23-H2 was responsible for the increase of c-myc transcription. Based on above experimental results, a new mechanism, involving G-quadruplex related CNBP/NM23-H2 interaction, for the regulation of c-myc transcription was proposed. These findings indicated that the regulation of c-myc transcription through NHE III1 region might be governed by mechanisms involving complex protein–protein interactions, and suggested a new possibility of CNBP as a potential anti-cancer target based on CNBP's biological function in c-myc transcription. •Cellular nucleic-acid-binding protein (CNBP) binds to oncogene c-myc promoter region.•We found that human CNBP bound to c-myc NHE III1 and promoted G-quadruplex formation.•CNBP induced a transient decrease followed by an increase in c-myc transcription.•Interaction of CNBP with NM23-H2 led to the increase of c-myc transcription.•New c-myc regulatory mechanism was proposed suggesting CNBP as an anti-tumor target.